Law Construction in Modern Society - Sofyan Arief (The Indonesian Journal of International Clinical Legal Education, 2019)
The effectiveness of law as a tool for social construction should ideally enhance our societal framework and address the challenges of the evolving era. However, contemporary observations reveal a growing lack of trust in the legal system. Critics point to perceived deficiencies in the quality of laws as agents of social construction and in achieving substantive justice. Moreover, a palpable anxiety surrounding a legitimacy crisis is evident. The role of law as a medium for social construction, aiming to establish a just and prosperous society, faces considerable resistance. Understanding the root causes behind society's struggle to interpret and embrace the purpose of law as a social construction instrument becomes imperative. The inadequate level of legal awareness among the populace is closely linked to issues such as educational disparities. The existing education systems, patterns of regulatory socialization, and restricted public access to information contribute to a diminished recognition of the importance of law. Addressing these challenges necessitates a focus on education as a viable solution. By elevating legal awareness, it is anticipated that the propensity for individuals to contravene the law would diminish. Therefore, investing in public education emerges as a promising strategy to foster the realization of a modern, constructively developed society.